Arithmetic
Associative Property
Averages
Brackets
Closure Property
Commutative Property
Conversion of Measurement Units
Cube Root
Decimal
Divisibility Principles
Equality
Exponents
Factors
Fractions
Fundamental Operations
H.C.F / G.C.D
Integers
L.C.M
Multiples
Multiplicative Identity
Multiplicative Inverse
Numbers
Percentages
Profit and Loss
Ratio and Proportion
Simple Interest
Square Root
Unitary Method
Algebra
Algebraic Equation
Algebraic Expression
Cartesian System
Linear Equations
Order Relation
Polynomials
Probability
Standard Identities & their applications
Transpose
Geometry
Basic Geometrical Terms
Circle
Curves
Angles
Define Line, Line Segment and Rays
Non-Collinear Points
Parallelogram
Rectangle
Rhombus
Square
Three dimensional object
Trapezium
Triangle
Trigonometry
Trigonometry Ratios
Data-Handling
Arithmetic Mean
Frequency Distribution Table
Graphs
Median
Mode
Range
Home >> Algebraic Expression >> Value of an Algebraic Expression >>

Value of an Algebraic Expression

 Addition Expression (Algebra) Division Expression (Algebra) Multipication Expression (Algebra) Subtraction Expression (Algebra) Terms of Algebraic Expression Value of an Algebraic Expression Tree Diagram for Algebraic Expression Constants Variables

Before you learn How to Find the Value of an Algebraic Expression,
you must know:

What are Constants ?
What are Variables ?

Value of an Algebraic Expression :-
By assigning values to variables in an algebraic expression, you can find the value of the expression.

From following examples you can learn How to Find The Value of an Algebraic Expression:-

Example 1 = Find the value of algebraic expression (p + q + r),
if (p = 1), (q = 2) and (r = 3)

Answer = The given algebraic expression is (p + q + r)
Put the respective values of (p = 1), (q = 2) and (r = 3) in the algebraic expression, and we get:
= 1 + 2 + 3
= 6
So The Value of the Given Algebraic Expression (p + q + r) is 6.

Example 2 = Find the value of algebraic expression (7x - 3y + 4),
if (x = 2) and (y = 3)

Answer = The given algebraic expression is (7x - 3y + 4)
Put the respective values of (x = 2) and (y = 3)in the algebraic expression, and we get:
= (7 X 2) - (3 X 3) + 4
Solve brackets and we get
= 14 - 9 + 4
Solve and we get:
= 9

So The Value of the Given Algebraic Expression (7x - 3y + 4) is 9.

Example 3 = Find the value of algebraic expression (8a ÷ 4b),
if (a = 2)and (b = 2)

Answer = The given algebraic expression is (8a ÷ 4b)
Put the respective values of (a = 2)and (b = 2) in the algebraic expression, and we get:
= (8 X 2) ÷ (4 X 2)
solve Brackets and we get:
= 16 ÷ 8
After division, we get:
= 2
So The Value of the Given Algebraic Expression (8a ÷ 4b) is 2.

Value of the given Algebraic expression is dependent on the value of it's variables

Or we can say that:
On the changing the value of variables, value of algebraic expression also changes.

Example : Find value of a + b + 4, if a = 2 and b = 3
Solution = The given algebraic expression is (a + b + 4)
Put the respective values of (a = 2) and (b = 3) in the given algebraic expression, and we get:
= 2 + 3 + 4
= 9
The Value of the Algebraic Expression a + b + 4 is 9, if a = 2 and b = 3....... (Statement 1)

Now lets change the value of variable i.e a = 1 and b = 5 in given algebraic expression i.e. a + b + 4. And observe the What happens ?

So here we again find the value of given algebraic expression a + b + 4 with a = 1 and b = 5
Put the respective values of (a = 1) and (b = 5) in the given algebraic expression, and we get:
= 1 + 5 + 4
= 10
The Value of the Algebraic Expression a + b + 4 is 10, if a = 1 and b = 5 ........ (Statement 2)

Hence from statement 1 and 2, you can observe that value of given algebraic expression changes when we change the values of its variable a and b.